2007
DOI: 10.1080/08910600701223942
|View full text |Cite
|
Sign up to set email alerts
|

The effects of food restriction on some biochemical parameters and certain bacterial groups in the cecum in Sprague Dawley rats

Abstract: Objective: Moderate food restriction, such as a 20 Á40% reduction of the ad libitum intake without causing malnutrition, delays or prevents morphological and functional changes related to aging and overnutrition. This study was performed to evaluate the effects of moderate to severe food restriction (20%, 40%, and 60% of ad libitum intake) for 28 days on some bacterial groups in the cecum and certain biochemical variables in male Sprague Dawley rats. Materials and methods: One group was allowed free access to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
1
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 40 publications
0
5
1
1
Order By: Relevance
“…The reasons are not well understood, but may relate to alterations in glucose transport function and the effects of increased free fatty acid concentrations on insulin utilization. Stress, as measured by increased cortisol concentrations, does not appear to be an important factor in this phenomenon, and serum cortisol concentrations did not change with fasting duration in our study. Previous studies in horses have identified insulin resistance after ≥17 hours of fasting .…”
Section: Discussioncontrasting
confidence: 44%
See 1 more Smart Citation
“…The reasons are not well understood, but may relate to alterations in glucose transport function and the effects of increased free fatty acid concentrations on insulin utilization. Stress, as measured by increased cortisol concentrations, does not appear to be an important factor in this phenomenon, and serum cortisol concentrations did not change with fasting duration in our study. Previous studies in horses have identified insulin resistance after ≥17 hours of fasting .…”
Section: Discussioncontrasting
confidence: 44%
“…Starvation and very low calorie diets have been shown to cause insulin resistance and diabetes in rodents and humans . The reasons are not well understood, but may relate to alterations in glucose transport function and the effects of increased free fatty acid concentrations on insulin utilization.…”
Section: Discussionmentioning
confidence: 99%
“…One possible explanation for the increased insulin concentrations appreciated during the third OST could be because of the effect of stress from multiple periods of fasting, environment change, and administration of each test. Stress from fasting and transport increased insulin concentrations in equids, although in another experimental model fasting did not affect cortisol levels . More research on the effect of environmental and handling stress on insulin concentration in horses is needed.…”
Section: Discussionmentioning
confidence: 89%
“…Stress from fasting and transport increased insulin concentrations in equids, although in another experimental model fasting did not affect cortisol levels. [43][44][45] More research on the effect of environmental and handling stress on insulin concentration in horses is needed.…”
Section: Oral Sugar Test Diagnostic Interpretationmentioning
confidence: 99%
“…However, various stress factors such as heat, cold, nutritional alterations, overcrowding, physical restraints and transporting or fouled or contaminated foods can destroy the microbial balance in the gastrointestinal system [66,67,[191][192][193][194][195] and alter their relationships with each other and with their hosts. Stressful stimuli can affect gastrointestinal microbiota directly, for example via limited availability of food ingredients or direct actions of stress mediators such as adrenaline or noradrenaline on microbiota [27,196], and indirectly via altering the intestinal environment of bacteria such as intestinal secretion, motility, permeability and immune functions as reviewed above.…”
Section: Stress and Intestinal Microbiotamentioning
confidence: 99%